2019
DOI: 10.1111/jcpe.13087
|View full text |Cite
|
Sign up to set email alerts
|

Secreted frizzled‐related protein 5 serum levels in human periodontitis—A nested case–control study

Abstract: Aim Recombinant secreted frizzled‐related protein 5 (sFRP5) improved periodontal status in mice. Thus, this study aimed to investigate this finding in human periodontitis using an epidemiological approach. Materials and Methods sFRP5 and wnt5a concentrations were determined in human serum from the Food Chain Plus cohort using ELISAs. A total of 128 patients with periodontitis and tooth loss and 245 patients with periodontitis without tooth loss were compared to 373 sex‐, smoker‐, age‐ and BMI‐matched individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Also, one study reported higher SOST protein levels in tissue samples from patients with moderate to severe periodontitis, while a similar trend, albeit not statistically significant, was seen for Wnt5a (77). When using a more permissive classification of periodontitis, the difference between disease and control tissues was not observed in samples from gingival crevicular fluid, suggesting that changes in the expression of Wnt5a might be highly restricted to the damaged site in severe periodontitis, thus explaining the absence of significant differences in serum samples (75).…”
Section: Wnt Signaling In the Periodontal Disease Changes At The Level Of Ligands Receptors And Modulators Of The Wnt Pathwaymentioning
confidence: 84%
See 1 more Smart Citation
“…Also, one study reported higher SOST protein levels in tissue samples from patients with moderate to severe periodontitis, while a similar trend, albeit not statistically significant, was seen for Wnt5a (77). When using a more permissive classification of periodontitis, the difference between disease and control tissues was not observed in samples from gingival crevicular fluid, suggesting that changes in the expression of Wnt5a might be highly restricted to the damaged site in severe periodontitis, thus explaining the absence of significant differences in serum samples (75).…”
Section: Wnt Signaling In the Periodontal Disease Changes At The Level Of Ligands Receptors And Modulators Of The Wnt Pathwaymentioning
confidence: 84%
“…One report measured Wnt5a levels in serum, failing to observe differences between subjects with and without periodontitis; however, there was higher expression of sFRP5 in patients without periodontitis, relative to patients with periodontitis followed by tooth loss, leading to changes in the sFRP5/Wnt5a ratio (75). In contrast, two independent studies (44,76) correlated an increased expression of WNT5A with a higher degree of periodontal destruction and observed lower expression of this ligand in healthy subjects.…”
Section: Wnt Signaling In the Periodontal Disease Changes At The Level Of Ligands Receptors And Modulators Of The Wnt Pathwaymentioning
confidence: 98%
“…In addition, the Sfrp5/Wnt5a axis might have a role in the association between periodontitis and systemic inflammatory disorders (including obesity, type 2 diabetes, and coronary artery disease). A nested case-control study found that in overweight individuals (body mass index, 24-38 kg/m²), Sfrp5 serum levels in patients with periodontitis involving tooth loss were significantly lower than in patients with periodontitis without tooth loss and the matched control group, while Wnt5a had no significant difference (48). Obese human subjects had significantly lower serum Sfrp5 levels than lean controls, while they had significantly higher serum Wnt5a levels (49).…”
Section: Wnt5a Triggers Proinflammatory Signaling Cascades and Increamentioning
confidence: 99%
“…The structure of SFRPs contains a netrin-like functional domain and a cysteine-rich domain, both of which are high homologous with the cysteine-rich domain of coiled protein and can compete with coiled protein to bind wingless-type family (Wnt) ligands, thus exerting a negative regulatory effect on the Wnt pathway [8]. SFRP5 has been identified as an anti-inflammatory adipokine, an endogenous inhibitor of Wnt5a signaling [8,9]. Previous studies unanimously reported that SFRP5 exerted an antiinflammatory effect by inhibiting the non-canonical Wnt5a/ c-Jun N-terminal kinase (JNK) signaling pathway, therefore playing a key role in repressing the occurrence and development of various diseases including obesity, cardiovascular diseases, and diabetes [10,11].…”
Section: Introductionmentioning
confidence: 99%